Moleque Cosmetics Sdn. Bhd / Amera Irrisya Fadzil Akhma ... [et al.] - Amera Irrisya, Fadzil Akhma; Nur Syuhada, Halmi; Muhammad Shazrul Haziq, Mohd Shafie; Muhammad Zulfadli, Muhammad Yasin; Muhammad Izzat Farhan, Mustapa (2019)
Being beauty and attractive is important for all the woman nowadays. Everyone want to be beautiful, but in this era globalization they always busy with their work and lifestyle so they have a lacks of time to take care of their skin. Makeup is the solution for all the woman that have a busy lifestyle. It can help all the woman daily life become easier and faster before going to works or any events. Nowadays, makeup have a high demand from consumers despite all range of age because beauty is important to make all woman feel more confident in whatever they do. This industry will help them to feel more confident and give them more good aura because our products is suitable for all types of ages.